Desenvolvimento de esponjas de luffa cylindrica com quitosana para adsorção do corante vermelho 40 - Schio, Rejiane da Rosa (2023)
The large consumption of water and the generation of colored effluents in industrial processes raise concerns regarding the pollution of water bodies. Containing this environmental pollution is one of the great challenges of modern society. Among the technologies used to treat colored effluents, adsorption stands out, which, combined with the use of adsorbents developed from natural sources, becomes an even more attractive technique. In this study, Luffa cylindrica (LC), a lignocellulosic material coveted for its versatility, was investigated to immobilize cross-linked chitosan and remove red dye 40 from aqueous solutions. The bioadsorbents were developed with different concentrations of chitosan (1%, 3% and 5% (m v-1)) and crosslinked agents (0.5%, 1.0% and 1.5% (v v-1))). The crosslinked agents studied were glutaraldehyde and epichlorohydrin as they behave differently with chitosan. And so, it resulted in LC with chitosan cross-linked with glutaraldehyde (LCsG) and LC with chitosan cross-linked with epichlorohydrin (LCsE). These materials were characterized regarding their physicochemical properties and then applied for adsorption studies. The characterizations demonstrated that LCsG and LCsE are amorphous materials, with irregular fibrous surfaces, very favorable for the adsorption process. The vibrational spectra showed that the chitosan successfully adhered to the Luffa surface and indicated that the cross-linking process took place for both cross-linking agents. The results regarding the degree of swelling and degree of crosslinking corroborated the assessment of the biosponge's adsorptive potential. Adsorption studies for red 40 removal were favored at pH 2. The pseudo-second order and Sips models satisfactorily represented the kinetic and isothermal data. Furthermore, the adsorption process was indicated to be spontaneous and endothermic. The maximum adsorption capacities were 77.66 mg g-1 for LC/CS/GLUT and 43.01 mg g-1 for LC/CS/EPIC. Furthermore, when reused, the adsorbents remained at about 70% of their original capacities after six adsorption cycles. In conclusion, materials prepared from Luffa cylindrica with chitosan resulted in promising natural adsorbents. Luffa cylindrica served as an excellent support for chitosan, resulting in an attractive adsorbent, with good adsorption potential and low cost.